Training of public activists, public sportsmen and mass sports referees from students - A., Abdullaev; J.I.Mamadaliev; A.A.Gafurov (Genius Journals, 2022)
The process of training of public activists on Physical Culture and sports - public sportsmen and judges of mass sports for selection methods and their training was expressed from the students.It is intended for future specialists in the field of Physical Culture and sports – bachelors and Masters and teachers of the subject of multi-disciplinary physical education
Keywords: Public; sports mass sports activist; physical culture activist; public sports referee